If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + 18 = 2u + 66 Reorder the terms: 18 + 4u = 2u + 66 Reorder the terms: 18 + 4u = 66 + 2u Solving 18 + 4u = 66 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 18 + 4u + -2u = 66 + 2u + -2u Combine like terms: 4u + -2u = 2u 18 + 2u = 66 + 2u + -2u Combine like terms: 2u + -2u = 0 18 + 2u = 66 + 0 18 + 2u = 66 Add '-18' to each side of the equation. 18 + -18 + 2u = 66 + -18 Combine like terms: 18 + -18 = 0 0 + 2u = 66 + -18 2u = 66 + -18 Combine like terms: 66 + -18 = 48 2u = 48 Divide each side by '2'. u = 24 Simplifying u = 24
| 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 | | 9x-(6x+9)=7x-29 | | 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 | | t+30=1 | | 5-2(2m+3)=15 | | 2(10x+3)=5(4x-7) | | -23=5k+7k | | 0.6x=0.4x+50 | | 2(5-3x)=9-6x | | -7.6=5.3+x+7.34 | | 4x+6(x+40)=180 | | 6t-32=7t-50 | | 5c=c+52 | | 3(2x-8)=2(3x+8) | | 2(sqrt(x))-5=x | | 7x-1=2x-3 | | 5-3x=3x-25 | | 527=31n | | 2x-3=6+2x | | -80.2-9x=1.7 | | 10x-75=51+4x | | o=5-(2x-17) | | x+3.07+2.5=1.8 |